Preparation and characterization of composite electrodes of coconut-shell-based activated carbon and hydrous ruthenium oxide for supercapacitors - Dandekar, M. S.; Arabale, G.; Vijayamohanan, K. (Journal of Power Sources, 2005)
The relationship between the structure-specific capacitance (F g(-1)) of a composite electrode consisting of activated coconut-shell carbon and hydrous ruthenium oxide (RuOx(OH)(y)) has been evaluated by impregnating various amounts of RuOx(OH)(y) into activated carbon that is specially prepared with optimum pore-size distribution. The composite electrode shows an enhanced specific capacitance of 250 F g(-1) in 1 M H2SO4 with 9 wt.% ruthenium incorporated. Chemical and structural characterization of the composites reveals a homogeneous distribution of amorphous RuOx(OH)(y) throughout the porous network of the activated carbon. Electrochemical characterization indicates an almost linear dependence of capacitance on the amount of ruthenium owing to its pseudocapacitive nature. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: activated carbon; Composite; Electrochemical characterization; pseudocapacitance; specific capacitance; supercapacitor

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Synthesis and characterization of polyimides and co-polyimides having pendant benzoic acid moiety - Kulkarni, M; Kothawade, S; Arabale, G.; Wagh, D; Vijayamohanan, K; Kulkarni, RA; Vernekar, SP (Polymer, 2005)
A novel diamine monomer, 2,4-diamino-4'-carboxy diphenyl ether had been synthesized. Several polyimides were prepared by reacting this diamine with commercially available dianhydrides, such as benzophenone tetracarboxylic acid dianhydride (BTDA), 4,4'bis{hexafluoroisopropylidene his (phthalic anhydride)} (6-FDA), oxydiphthalic anhydride (ODPA) and 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (BPDA). Furthermore, copolymers from the resulting diamine and oxydianiline (ODA) with 6 FDA were also synthesized. The inherent viscosities of the polymers were 0.42-0.67 dl g(-1). The polymers have good solubility in polar aprotic solvents, high thermal stability up to 410 &DEG; C in nitrogen and high glass transition temperatures (T-g) ranging from 260-330 &DEG; C. These polymers formed tough flexible films by solution casting. © 2005 Elsevier Ltd. All rights reserved.
Keywords: co-polyimides; diamine with pendant benzoic acid; polyimides with pendant benzoic acid